Stressors impair odor recognition memory via an olfactory bulb-dependent noradrenergic mechanism - Manella, Laura C.; Alperin, Samuel; Linster, Christiane (Frontiers in Integrative Neuroscience, 2013)
Non-associative habituation and odor recognition tasks have been widely used to probe questions social recognition, odor memory duration, and odor memory specificity. Among others, these paradigms have provided valuable insight into how neuromodulation, and specifically norepinephrine/noradrenaline (NE) influences odor memory. In general, NE levels are modulated by arousal, stress, and behavioral state, and there is sparse evidence of a direct relationship between NE and odor memory in adult rodents. The present study uses simple mild psychological stressors (bright light and sound), to modulate NE levels physiologically in order to probe its effect on olfactory memory. In rats with bilateral bulbar cannulations, we show that these stressors modulate olfactory memory and that this effect is at least partially mediated by olfactory bulb. Specifically, we show that the presence of stressors during the acquisition of odor memory suppresses memory for an odor when tested 30 minutes after the acquisition. This suppression is blocked by infusing NE antagonists into the olfactory bulb prior to odor acquisition. Additionally, we find that infusion of bulbar NE is sufficient to suppress odor memory in a manner mimicking that of our stressors. These effects are unlikely to be solely mediated by locomotor/exploratory changes produced by stressors, although these stressors influence certain behaviors not directly related to odor investigation. This study provides important information about how behaviorally relevant changes in NE can influence top-down sensory processing and odor memory.